Main Aspects of Pharmaceutical Development of In situ Immunobiological Drugs for Intranasal Administration - Bakhrushina, Elena; Mikhel, Iosif; Kondratieva, Valeriya; Demina, Natalia; Grebennikova, Tatyana; Krasnyuk Jr, Ivan; Krasnyuk, Ivan (Current Pharmaceutical Biotechnology, 2024)
Introduction: The review presents the latest developments in the area of intranasal in situ delivery systems of immunobiological drugs (IBDs). Interest in intranasal administration for IBDs has increased significantly due to the COVID-19 pandemic. However, not only intranasal delivery of vaccines is developing, but also bacteriophages, interferons, etc. In situ systems that make a selective phase transition can be a modern solution to intranasal delivery problems caused by mucociliary clearance. In addition, smart-polymers used as the main excipients in in situ systems can be used as specific adjuvants. Methods: A scientific search was conducted on the PubMed database of medical publications for the period from 2000 to 2022, using the keywords
Keywords: bacteriophages